DEVELOPING CHANGE LEADERS IN COMMUNITY DEVELOPMENT IN DONG KHRANG NOI SUBDISTRICT KASET WISAI DISSICT ROI ET PROVINCE - Barisri, Jirapon; Kenaphoom, Sanya (Journal of Social Science and Cultural, 2023)
Research article on the development of change leaders in community development in Dong Khrang Noi Subdistrict. Its purpose is to 1) study the level of change leadership 2) study the level of community development 3) analyze change leaders that affect community development and 4) propose guidelines for developing change leaders. The study area is Dong Khrang Noi Subdistrict. It is quantitative research and qualitative research. Quantitative research The sample group consisted of 366 people in the Dong Khrang Noi Subdistrict community using probability sampling. The research tools used were questionnaires, qualitative research, identifying key informants, including district chiefs, district development officers, sub-district NFE heads, kamnans, village headmen, academics, professional group presidents, village health volunteers presidents, village committee representatives, a total of 15 people. By choosing a specific model Data were collected through in-depth interviews. Statistics used included percentages, averages, and standard deviations. Pearson correlation, multiple prediction and content analysis synthesis. The results of the research found that 1) The leader of change in Dong Khrang Noi Subdistrict is taking into account the individuality of each person. inspiration Intellectual stimulation 2) The development of Dong Khrang Noi Subdistrict community is the development of natural resources. and the environment, education, and promoting quality of life. 3) Change leaders who affect community development include intellectual stimulation, having influence with ideology, inspiring inspiration, and considering individuality which together predict community development at 80.90% 4) Guidelines for developing change leaders as follows: (1) having influence with ideology, (2) inspiring, (3) intellectually stimulating, and (4) Taking into account individuality